GUIDELINES FOR INCREASING EFFICIENCY IN THE USE OF INFORMATION TECHNOLOGY FOR THE WORK OF ELDERLY ACCOUNTANTS IN INDUSTRIAL BUSINESS - Thawilpol, Thanatchaporn (Journal of Buddhist Anthropology, 2021)
The objectives of this research article was to analyze confirmatory factors of guidelines for increasing efficiency in the use of information technology for the work of elderly accountants in the industrial business. A quantitative research method was applied to this research. The research population was 500 entrepreneurs or executives in the industrial industry. In total, 500 samples were selected through a simple random sampling method. The data was collected by a questionnaire. The descriptive statistics used for data analysis were percentage, mean, and standard deviation. Moreover, the inferential statistical analysis was a confirmatory factor analysis (CFA). The results revealed that the guidelines for increasing efficiency in using technology for the work of elderly accountants in the industrial business comprised three constructs. Firstly, the perceived usefulness (PU), containing six items, had the highest impact on efficiency in using information technology, with the regression weight between 0.52 and 0.67. According to the results, awareness of information technology increases the effectiveness of accounting to be more accurate and complete (0.67). Meanwhile, the attitude towards using (ATU) comprised four items with the regression weight between 0.32 and 0.69. There is a belief that the use of information technology is beneficial to accounting (0.69). Lastly, the actual system use (ASU) consisted of four items with the regression weight between 0.70 and 0.80. When implementing information technology, it can meet the needs of the users completely (0.80). The results of model consistency validation revealed that the model of guidelines for increasing efficiency in the use of information technology for the work of elderly accountants in industrial business was consistent with the empirical data.